(untitled) (The Nepalese Management Review, 2024)
The rise of female entrepreneurs is a significant development, as they play a crucial role in driving economic growth. This is especially important in developing countries like Nepal, where it can also help to reduce unemployment. However, many women entrepreneurs need help with their cultural environment when starting or managing their businesses. This paper explores the multifaceted impact of culture on the entrepreneurial behavior of women. Entrepreneurship is a dynamic and complex phenomenon influenced by various factors, and cultural context plays a crucial role in shaping an individual’s attitudes, motivations, and decisions. The study focuses specifically on how cultural dimensions such as societal norms, gender roles, and cultural values interact to shape women’s entrepreneurial behavior. The research methodology involves a comprehensive review of the existing 50 articles on women’s entrepreneurship and their sociocultural intervention on the behavior of women entrepreneurs. The findings reveal that cultural factors significantly influence women’s entrepreneurial intentions, risk perceptions, and business strategies. Societal expectations and gender norms can either facilitate or hinder women’s entry into entrepreneurship, affecting their confidence, risk-taking propensity, and access to resources. Moreover, cultural values such as collectivism or individualism impact networking patterns, collaboration tendencies, and leadership styles among women entrepreneurs.